Escala de Identidade Ambientalista: uma ferramenta para descobrirmos que ambientalistas somos - Seixas, Paulo Castro; Dias, Ricardo Cunha; Vidal, Diogo Guedes (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
This article proposes a Scale that enables a reflective discussion of environmentalist identity profiles. Environmentalism is a central element of 21st century identity and, however, the literature fails in environmentalist typologies that allow reflection and positions on the topic. The methodology followed in this work implied a historical analysis of environmentalism. Such analysis resulted in 8 subscales that are aggregated in a single methodological instrument: the Environmentalist Identity Scale (EIA). The main contribution is to provide a simple instrument that allows a reflexive approach of each subject to a set of ideal types of environmentalist identities, supporting active intervention methodologies.